Strength in Numbers or Stronger Alone. How does the Portrayed Idea of Sovereignty influence the Icelandic Political Parties’ Stance towards the European Union? - Kolbeinn Atli Björnsson 1979- (2011)
Sovereignty is a critical concept when it comes to discussion in Iceland about the nation‟s participation in European cooperation, be it the European Union, the European Free Trade Association or Iceland‟s involvement in the Schengen Agreement. The sovereignty debate tends to be heavily influenced by references to the country‟s fight for independence in the late eighteenth and early nineteenth centuries, ideas of nationality, and attitude towards the rest of the world. In this thesis the focus will be on the four major Icelandic political parties and the question will be put forth, whether each party‟s use of the concept of sovereignty can explain their stance on the question of Iceland‟s possible membership to the European Union. For this purpose, official party publications, and other party literature on possible Icelandic membership to the European Union will be studied using critical evaluation and review. The thesis‟s main conclusions are that a post-Westphalian view on sovereignty used by the Social Democratic Alliance translates into a positive stance on joining the European Union. The classical Westphalian view, used by the Independence Party and currently the Progressive Party, translates to a negative attitude towards whether Iceland should join the European Union.